1989
DOI: 10.1073/pnas.86.23.9228
|View full text |Cite
|
Sign up to set email alerts
|

Aspartic acid-96 is the internal proton donor in the reprotonation of the Schiff base of bacteriorhodopsin.

Abstract: Above pH 8 the decay of the photocycle intermediate M of bacteriorhodopsin splits into two components: the usual millisecond pH-independent component and an additional slower component with a rate constant proportional to the molar concentration of HI, 1H+]. In parallel, the charge translocation signal associated with the reprotonation of the Schiff base develops a similar slow component. These observations are explained by a two-step reprotonation mechanism. An internal donor ru-st reprotonates the Schiffbase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
351
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(372 citation statements)
references
References 19 publications
20
351
1
Order By: Relevance
“…1d). UV-visible spectroscopy 26 has shown that the lifetime of the M-intermediate of D96N and WT is prolonged at alkaline pH; in concordance with this fact is the observation here with D96N that the decay detected by high-speed AFM showed a strong pH dependence (inset, Fig. 1d).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…1d). UV-visible spectroscopy 26 has shown that the lifetime of the M-intermediate of D96N and WT is prolonged at alkaline pH; in concordance with this fact is the observation here with D96N that the decay detected by high-speed AFM showed a strong pH dependence (inset, Fig. 1d).…”
supporting
confidence: 87%
“…We used the D96N bR mutant, which has a longer photocycle (~10 s) than that of WT (~10 ms) but retains proton pumping ability 26 . Figure 1a We analyzed the "mass center" positions of the individual monomers imaged during the dark-illumination cycles.…”
mentioning
confidence: 99%
“…If the fatty acid is complementing the loss of the D132 carboxyl, or interacting at another site to improve proton access, this resembles the chemical rescue phenomenon observe with carboxylate mutants of other proton transferring membrane proteins. In mutated bacteriorhodopsin [14,15] and bacterial photosynthetic reaction center [16] activity can be restored by weak acid anions such as azide. These water soluble acids are required at much higher concentrations (approaching molar), as opposed to micromolar for the fatty acid effects.…”
Section: Fatty Acid Stimulation Of Activity and Restoration Ofmentioning
confidence: 99%
“…The 1.5 ms component in the M-decay of V101C-AF is most likely due to the M-to-N/O transition, in which the Schiff base is reprotonated from aspartate-96 [2,3]. The 63.9 ms component is probably due to the decay of N and O which are coupled to the M-decay by back reactions [16]. This is supported by photocycle measurements at 650 nm (data not shown), which indicate that O returns to the initial state with a decay time of 61.7 ms.…”
Section: Resultsmentioning
confidence: 98%